Evaluation of 1.25Cr0.5Mo steel behaviour in creep conditions: Evaluation of 1.25Cr0.5Mo steel behaviour in creep conditions - Fernández-Fuentes , Alfonso Rafael; Cruz-Crespo , Amado; Scotti , Americo; Guedes-De Alcãntara, Nelson (Rev. Téc. Fac. Ing. Univ. Zulia, 2021)
Studies about the influence of the post weld heat treatment on microstructures and mechanical behaviors of steam pipelines have focused on the weld region (fusion and heat-affected zones). However, this process has a thermal effect that surpasses this region, which has not been sufficiently detailed. The aim of the present work consisted in evaluating the effect of the heat treatment on the microstructure and creep behavior in the region that is not affected by welding thermal cycle. The analyzed material was taken from a main steam pipe (1.25Cr0.5Mo steel, 20 years in service aged at 480 oC). A piece of the pipeline was subjected to heat treatment, with parameters according to the ASME boiler and pressure vessel code. The creep rupture time and the microstructure were obtained from the in service aged material, as well as from the heat-treated one. The heat treatment of in service aged 1.25Cr0.5Mo steel increased the amount of the inside ferrite grain precipitates and reduced the creep resistance.